2009
DOI: 10.2147/opth.s4820
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of surgically induced miosis and prevention of postoperative macular edema with nepafenac

Abstract: Objective:To evaluate the effectiveness of prophylactic administration of nepafenac 0.1% in maintaining mydriasis and in preventing postoperative macular edema following cataract surgery.Methods:This was a prospective, randomized, single-masked comparative study in 60 patients undergoing phacoemulsification cataract surgery. Patients were randomized to either the nepafenac or the control group. Nepafenac was administered 3 times daily 1 day before surgery and continued for 6 weeks. The control group received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 34 publications
5
33
1
7
Order By: Relevance
“…These results were similar to those of Cervantes-Coste et al, who also found that the prophylactic use of nepafenac 0.1% was safe and effective in maintaining mydriasis during cataract surgery. 16 The use of topical prednisolone 1% to maintain the intraoperative mydriasis was superior to placebo. Shaikh et al, analyzed the antimiotic effect of topical prednisolone and flurbiprofen.…”
Section: Discussionmentioning
confidence: 98%
“…These results were similar to those of Cervantes-Coste et al, who also found that the prophylactic use of nepafenac 0.1% was safe and effective in maintaining mydriasis during cataract surgery. 16 The use of topical prednisolone 1% to maintain the intraoperative mydriasis was superior to placebo. Shaikh et al, analyzed the antimiotic effect of topical prednisolone and flurbiprofen.…”
Section: Discussionmentioning
confidence: 98%
“…2015): maintenance of mydriasis during ophthalmic surgery (Cervantes‐Coste et al. 2009; Zanetti et al. 2012; Sarkar et al.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the present study, Flurbiprofen was administered 1 day preoperatively; however, whether administration 3 days prior to surgery would make any difference in the outcome is something that should be evaluated in the future. Due to the advances in surgical techniques there may be less tissue trauma and this may be the reason for preoperative use of Flurbiprofen being not statistically significant in decreasing intraoperative miosis.…”
mentioning
confidence: 89%
“…3,4 In addition, non-steroidal anti-inflammatory drugs (NSAIDs), which directly inhibit the COX enzymes with the resultant inhibition of PG release are used to prevent surgically induced miosis. 5 The intraoperative…”
Section: Introductionmentioning
confidence: 99%